Comparison of impact resistance of carbon fibre composites with multiple ultra-thin CNT, aramid pulp, PBO and graphene interlayers. (April 2022) - Hu, Yunsen; Wei, Yang; Han, Gang; Zhang, Jingheng; Sun, Guangyong; Hu, Xiaozhi; Cheng, Fei
Highlights: CNT, aramid Pulp, PBO and graphene were used for CFRP toughening. Low-velocity impact, compression and compression after impact tests were conducted. The residual compressive strength of reinforced CFRPs improved by 8.1–37.8%. Ultra-thin interlayers had no adverse effects on composite compressive properties. Abstract: This study compared the impact properties of carbon fibre reinforced polymer (CFRP) laminates with multiple ultra-thin interlayers of multi-wall carbon nanotubes (CNTs) Aramid pulp (AP) micro/nano-fibres, poly (p-phenylene-2, 6-benzobisoxazole) (PBO) fibres (from nano- to micro/nano- and micro-fibres) and multi-layer graphene. The low-velocity impact results showed that the impact damage was notably reduced in all reinforced laminates except the graphene reinforced laminate. Compression after impact tests were conducted on these impacted specimens, showing 8.1–37.8% improvements in residual compressive strength from different micro- and nano-filler reinforcements. While improving the impact resistance, those ultra-thin interlayers with around 1.6 g per square meter of micro/nano-reinforcements were controlled around 8 μm in thickness and did not have any adverse effect on compressive properties of CFRP laminates even without any impact damage.